2020
DOI: 10.3390/nu12113542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xylo-Oligosaccharides Supplementation by Drinking Water on the Bone Properties and Related Calcium Transporters in Growing Mice

Abstract: Xylo-oligosaccharides (XOS), non-digestible oligosaccharides, have the potential to regulate intestinal microorganisms, and thus, improve host health, but little evidence exists for the prebiotic effects on bone health. This study evaluates the dose-response effect of XOS supplementation on bone properties, the morphology of the intestine, cecum pH, and cecum wall weight, as well as the related calcium transporters. Ninety-six 28-day-old male mice were randomized into one of four groups, fed the same commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The finding is consistent with a former study who also observed an increased Trpv6 level in the duodenum of mice after xylo‐oligosaccharides intervention. [ 9 ] A possible mechanism is that SCFAs in cecum stimulate the expression of Trpv6. [ 9 ] In addition, inulin also enhanced the expression of Aqp8, which is a channel regulating water absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding is consistent with a former study who also observed an increased Trpv6 level in the duodenum of mice after xylo‐oligosaccharides intervention. [ 9 ] A possible mechanism is that SCFAs in cecum stimulate the expression of Trpv6. [ 9 ] In addition, inulin also enhanced the expression of Aqp8, which is a channel regulating water absorption.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] A possible mechanism is that SCFAs in cecum stimulate the expression of Trpv6. [ 9 ] In addition, inulin also enhanced the expression of Aqp8, which is a channel regulating water absorption. Enhanced water absorption across GI tract may accelerate passive calcium absorption by concentrating Ca 2+ in intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XOSs are prebiotics composed of 2–7 xylose molecules fostering Bifidobacteria over Lactobacillus [ 63 ]; in mice, they increase calcium uptake by upregulating the expression of transient receptor potential vanillin receptor 6 (TRPV6) and Na + /Ca 2+ exchanger in the duodenum, and increase BMD [ 64 ]; they also reduce bone loss in high-fat-diet insulin-resistant mice [ 65 ], and decrease inflammation markers.…”
Section: Effects Of Dietary Supplements On the Gut Microbiota And Bon...mentioning
confidence: 99%
“…Prebiotics also enhance bone mass by decreasing intestinal permeability and thus preventing systemic inflammation ( Zhang et al, 2021 ). Xylo-oligosaccharides (XOS) treatment was observed to increase BMD by upregulating the expression of Ca transporters in the intestine ( Gao and Zhou, 2020 ). It is reported that FOS also enhances osteogenesis and thus induces bone formation.…”
Section: Dietary Interventions and Modulation Of Gut Microbiotamentioning
confidence: 99%